Penaeus monodon IKKs Participate in Regulation of Cytokine-Like System and Antiviral Responses of Innate Immune System - Nhnhkorn, Zittipong; Amparyup, Piti; Kawai, Taro; Tassanakajon, Anchalee (Frontiers in Immunology, 2019)
The IKK-NF-κB signaling cascade is one of the crucial responsive mechanisms in inflammatory and immune responses. The key kinase proteins called inhibitor of kappa B kinases (IKKs) serve as the core elements involved in cascade activation. Here, the complete ORFs of IKK homologs, PmIKKβ, PmIKKε1 and PmIKKε2, from the black tiger shrimp Penaeus monodon were identified and characterized for their functions in shrimp antiviral responses. The PmIKK transcripts were widely expressed in various examined tissues and the PmIKKε protein was detected in all three types of shrimp hemocytes. Only the PmIKKε1 and PmIKKε2 were responsive to white spot syndrome virus (WSSV), yellow head virus (YHV) and a bacterium Vibrio harveyi infection, while the PmIKKβ exhibited no significant response to pathogen infection. On the contrary, suppression of PmIKKβ and PmIKKε by dsRNA-mediated RNA interference (RNAi) resulted in a rapid death of WSSV-infected shrimp and the significant reduction of an IFN-like PmVago4 transcript. Whereas the mRNA levels of the antimicrobial peptides, ALFPm3 and CrustinPm5, and a transcription factor, PmDorsal were significantly increased, those of ALFPm6, CrustinPm1, CrustinPm7, PmVago1, PmRelish and PmCactus were unaffected. Overexpression of PmIKKβ and PmIKKε in HEK293T cells differentially activated the NF-κB and IFNβ promoter activities, respectively. These results suggest that the PmIKKβ and PmIKKε proteins may act as a common factors regulating the expression of immune-related genes from various signaling pathways. Interestingly, the PmIKKs may also contribute a possible role in shrimp cytokine-like system and cross-talking between signaling transductions in innate immune responses.